2011
DOI: 10.1177/1470320311422581
|View full text |Cite
|
Sign up to set email alerts
|

Spironolactone improves nephropathy by enhancing glucose-6-phosphate dehydrogenase activity and reducing oxidative stress in diabetic hypertensive rat

Abstract: Spironolactone (SPR), a mineralocorticoid receptor blocker, diminishes hyperglycemia-induced reduction in glucose-6-phosphate dehydrogenase (G6PD) activity, improving oxidative stress damage. This study investigated whether SPR ameliorates nephropathy by increasing G6PD activity and reducing oxidative stress in spontaneously hypertensive diabetic rats (SHRs). The streptozotocin-induced diabetic rats received or not SPR 50 mg/kg per day, for eight weeks. A human mesangial cell line was cultured in normal or hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 27 publications
0
25
0
Order By: Relevance
“…Although urinary 8-OHdG was observed to be partially decreased after SPL treatment (38), SPL had no effect on the expression of Bcl-2/Bax, p-AKT/total AKT protein, iNOS, NADPH oxidase, p22phox, and p67phox in db/db mice islets or MIN6 cells. This indicates that SPL has limited antioxidant activity.…”
Section: Discussionmentioning
confidence: 60%
“…Although urinary 8-OHdG was observed to be partially decreased after SPL treatment (38), SPL had no effect on the expression of Bcl-2/Bax, p-AKT/total AKT protein, iNOS, NADPH oxidase, p22phox, and p67phox in db/db mice islets or MIN6 cells. This indicates that SPL has limited antioxidant activity.…”
Section: Discussionmentioning
confidence: 60%
“…Some previous reports have shown that MRBs exerted no beneficial effects or even led to the aggravation of hyperglycemia and metabolic syndrome [5][6][7][8][9][10], but other studies have shown that spironolactone treatment ameliorated insulin resistance in obese mice or in diet-induced metabolic syndrome [11,12]. Some previous reports have shown that MRBs exerted no beneficial effects or even led to the aggravation of hyperglycemia and metabolic syndrome [5][6][7][8][9][10], but other studies have shown that spironolactone treatment ameliorated insulin resistance in obese mice or in diet-induced metabolic syndrome [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Researches are being focused on targeting different T-regulatory cells which can suppress pro-inflammatory response via attenuation of respective signalling cascades. Experiments on different animal models have demonstrated their efficacy in treating oxidative stress induced DN [184]. Interestingly, studies on human with some of these molecules have also shown positive results.…”
Section: Current Status and Future Prospect Of Antioxidant Therapies mentioning
confidence: 99%
“…SPL exposure has shown to down regulate TGF-β expression and hence it inhibits oxidative stress in renal cortex of diabetic rats [183]. Therefore, it can be said that SPL can function as an antioxidant compound by elevating anti-oxidative defense systems (like GSH level) and thereby reducing oxidative stress [184]. However, the limitation of SPL administration is that its protective action is effective at early stages of DN but it has no beneficial effect at later stages of the disease [185,186].…”
Section: Spironolactonementioning
confidence: 99%